(3CSbW aj faSj s - AlGhanem, Nujoom (3GdZGfe, fLhes ((3HjQhJ; CQOf;s (3GdeDSSI GdYQHjI ddOQGSGJ h GdfTQ;s, 2012)
Selection of work.
Title translation: Angels of distant longings- Nujoom Al Ghanem
Arabic
Keywords: PN1010-1525 Poetry; UAE